2015
DOI: 10.1118/1.4926550
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative correlational study of microbubble‐enhanced ultrasound imaging and magnetic resonance imaging of glioma and early response to radiotherapy in a rat model

Abstract: Purpose: Radiotherapy remains a major treatment method for malignant tumors. Magnetic resonance imaging (MRI) is the standard modality for assessing glioma treatment response in the clinic. Compared to MRI, ultrasound imaging is low-cost and portable and can be used during intraoperative procedures. The purpose of this study was to quantitatively compare contrast-enhanced ultrasound (CEUS) imaging and MRI of irradiated gliomas in rats and to determine which quantitative ultrasound imaging parameters can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…PI indicated the maximum number of microbubbles in the capillaries, so it represented the number of capillaries. PIT indicated the number of capillaries in the entire testicle, and AUCT indicated the microbubble distribution in the entire testicle [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…PI indicated the maximum number of microbubbles in the capillaries, so it represented the number of capillaries. PIT indicated the number of capillaries in the entire testicle, and AUCT indicated the microbubble distribution in the entire testicle [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…31 Pre-clinical, these more advanced MR techniques were used by the MR research group at John Hopkins University for the assessment of response to RT in a rat model of GB. [32][33][34] Hong et al 34 performed longitudinal quantitative multiparametric MRI, in addition to standard T 2 weighted MR. The quantitative MR sequences included T 1 relaxometry, T 2 relaxometry, diffusion-weighted imaging (DWI), arterial spin labelling and chemical exchange-dependent saturation transfer (CEST) techniques.…”
Section: Mr-guided Rt In Animal Models Of Glioblastomamentioning
confidence: 99%
“…This research group also compared their multiparametric MR approach to contrast-enhanced ultrasound imaging (CEUS) and observed that several CEUS-based metrics correlated well with MR-based metrics. 33 They summarised that CEUS might be a low-cost and portable alternative to multiparametric MR for the assessment of treatment response.…”
Section: Mr-guided Rt In Animal Models Of Glioblastomamentioning
confidence: 99%
“…Glioma is the most common and fatal type of primary brain tumors (Gusyatiner and Hegi 2018 ). Glioblastoma (GBM) accounts for 60–70% of these malignancies (Yang 2015 ) and has an average survival time of 12–15 months (Alexander and Cloughesy 2017 ). Due to the unique anatomical position and moderate radiosensitivity of tumors, radiotherapy (XRT) has been playing a leading role in the treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%